EQUILIBRIUM ANALYSIS OF FLAT ELEMENTS OF THE SAW WORKING ELEMENT PACKAGE - ABDUVAKHIDOV, MUTAKHKHIRKHON (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In the article, one of the most important results is that the magnitude of the bending rigidity of the saw working element package is a function of only the magnitude of the compression force of the package and the geometric dimensions of the contact areas of the flat elements, but does not depend on the mechanical properties of the materials of the rod elements. Here, a certain analogy can be traced with the linear rigidity of a flexible thread, determined only by the magnitude of its stretching force and also independent of the properties of the thread material.